Development of Reading Instructional Model using Task-based Language Teaching Approach integrating with Discourse-oriented Strategies to Enhance Reading Abilities of Undergraduate Students - Ngerndee, Hathaichanok; Chattiwat, Wisa (วารสารบัณฑิตศาส์น มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2019)
The purposes of this study were to; 1. construct the Reading Instructional Model using Task-based Language Teaching Approach integrating with Discourse-oriented strategies to enhance Reading abilities of undergraduate students and to investigate the efficiency based on the assigned criteria 80/80, 2) compare students’ reading abilities before and after using the Reading Instructional Model, 3) study the discourse-oriented strategies used by students while reading expository texts, 4) explore students’ satisfaction towards the Reading Instructional Model, and 5) verify the Reading Instructional Model using Task-based Language Teaching Approach integrating with Discourseoriented strategies The subjects were 40 first year students, Faculty of Political Science, who registered in the second semester of academic year 2016, Burapha University by simple random sampling. The experiment took place during a period of 16 weeks. The research instruments consisted of; 1) 8 units of lesson plans, exercises, and a teacher’s manual, 2) reading comprehension test, 3) self-report questionnaire, 4) think-aloud protocol, 5) satisfaction questionnaire, and 6) interviewed questions. The t-test for dependent, mean, percentage, and standard deviation were used for data analysis. This research was carried out using the mixed-method approach. The results of the study revealed as follows: 1. The Reading Instructional Model using Task-based Language Teaching Approach Integrating with Discourse-oriented Strategies to enhance Reading abilities of undergraduate students comprised four components: principles, objectives, learning and teaching procedures, and evaluation. The Model called "NODE Model" featured four steps: noticing (N), orienting (O), doing task (D), and evaluating (E). The NODE model was verified to be at a very good level by five experts, and met the expected criterion (80/80). 2. The score of students’ reading comprehension posttest was significantly higher than pretest at 0.05 level, and the sample group reading abilities improved. 3. The results indicated that the most popular discourse-oriented strategies that students used while reading expository texts were previewing text structure and recognizing main idea respectively. 4. The students’ satisfaction towards the Reading Instructional Model was at a very high level, and they used their potential to do the task-based activities with enjoyment. 5. The verification of the Reading Instructional Model using Task-based language teaching approach integrating with discourseoriented strategies was at the highest congruence to the theories’ rationality and probability. The theories’ rationality was at a high level ( x̄= 4.60, S.D. = 0.49) and mean score of the probability was x̄= 4.80, S.D. = 0.40 The congruence of the Reading Instructional Model was at a high level ( x̄= 4.80, S.D. = 0.40) respectively.